2012
DOI: 10.1258/jtt.2012.120404
|View full text |Cite
|
Sign up to set email alerts
|

An online positive parenting skills programme for paediatric traumatic brain injury: feasibility and parental satisfaction

Abstract: We examined the feasibility of and parental satisfaction with a training programme for parents with children who had suffered traumatic brain injury (TBI). Families who did not have a home computer and/or webcam were loaned the necessary equipment. Skype was used for videoconferencing. After the initial treatment session in the family's home, the remaining nine sessions were conducted online. Each session had two parts: (1) a self-guided web session with information about a particular skill; (2) a videoconfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 17 publications
4
36
0
Order By: Relevance
“…However, they demonstrated high intervention completion rates (71%) consistent with, and in some cases higher than, other PCIT studies (e.g., Antonini et al, 2012;Boggs et al, 2005;Schuhmann et al, 1998;Werba & Eyberg, 2006). Moreover, completion rates for the current study fare well relative to other evidenced-based parent training programs with attrition rates approaching 50% (Reyno & McGrath, 2006), and family-focused TBI interventions with attrition rates between 56% and 76% (Antonini et al, 2014(Antonini et al, , 2012. Notably, caregivers who dropped out of the intervention endorsed multiple psychosocial stressors during the time they were enrolled in the study, which may have contributed to their inability to complete the intervention.…”
Section: Summary Of the Current Worksupporting
confidence: 78%
See 3 more Smart Citations
“…However, they demonstrated high intervention completion rates (71%) consistent with, and in some cases higher than, other PCIT studies (e.g., Antonini et al, 2012;Boggs et al, 2005;Schuhmann et al, 1998;Werba & Eyberg, 2006). Moreover, completion rates for the current study fare well relative to other evidenced-based parent training programs with attrition rates approaching 50% (Reyno & McGrath, 2006), and family-focused TBI interventions with attrition rates between 56% and 76% (Antonini et al, 2014(Antonini et al, , 2012. Notably, caregivers who dropped out of the intervention endorsed multiple psychosocial stressors during the time they were enrolled in the study, which may have contributed to their inability to complete the intervention.…”
Section: Summary Of the Current Worksupporting
confidence: 78%
“…Further, contrary to expectations that an online parenting intervention would be more accessible to families and lead to better completion rates than standard parenting interventions, Antonini et al (2012) reported high rates of no-shows and cancellations, and completion rates that were consistent with PCIT studies implemented in the clinic (Schuhmann, Foote, Eyberg, Boggs, & Algina, 1998). These challenges to maintaining gains and maximizing intervention adherence suggest an adaptation of PCIT to address the needs of high-risk families of children with TBI may be warranted.…”
Section: Consistent With Recommendations To Examine Established Intermentioning
confidence: 70%
See 2 more Smart Citations
“…Antonini et al [27] describe the results with an online positive parenting skills program for parents of children with TBI. Skype was used for videoconferencing and additional online sessions were available.…”
Section: Computer Assisted Technologymentioning
confidence: 99%